Vertical dispersal of Aedes (Stegomyia) spp. in high-rise apartments in Putrajaya, Malaysia - Wan-Norafikah, Othman; Nazni, Wasi Ahmad; Noramiza, S.; Shafa'ar-Ko'ohar, S.; Azirol-Hisham, A.; Nor-Hafizah, R.; Sumarni, M.G.; Mohd-Hasrul, H.; Sofian-Azirun, Mohd; Lee, H.L. (Malaysian Society of Parasitology and Tropical Medicine, 2010)
A preliminary study on the vertical dispersal of Aedes populations in high-riseapartments was carried out in Presint 9, Putrajaya, Malaysia. Ovitraps were placed indoorswithin four blocks of high-rise apartments from the ground floors (0.0 – 3.0 m) until upto the tenth floors (28.1 – 30.0 m). Aedes aegypti was the dominant species found in theovitraps (87.85%), while Aedes albopictus was found in lower numbers. From total numberof larvae collected (650), 40.92% of these larvae were obtained from the fourth block;Block D. The peak density of Aedes sp. was observed at level 6 (16.1 – 18.0 m), whileAe. aegypti was found until the tenth floor (28.1 – 30.0 m). In contrast, Ae. albopictuswas found only up to the sixth floor (16.1 – 18.0 m). A poor correlation of the meannumber of Aedes larvae collected with the level of high-rise apartments occupied (N=40;ρ=-0.349) was also observed which indicated the possibility of lesser Aedes populationsto be found at higher level of high-rise apartments. Therefore, larger scale studies arestrongly recommended to examine the vertical dispersal of Aedes mosquitoes.